Tools for Peace: The Spiritual Craft of St. Benedict and René Girard - Slater, Isaac (Cistercian studies quarterly, 2010)
The article reviews the book "Tools for Peace: The Spiritual Craft of St. Benedict and René Girard," by Andrew Marr.